2023
DOI: 10.1002/jclp.23534
|View full text |Cite
|
Sign up to set email alerts
|

Associations of resilience and hope with mental and physical health among firefighters

Abstract: Objective Firefighters represent an understudied population with high rates of chronic exposure to stress and potentially traumatic events. Thus, there is a need to identify modifiable resilience factors to address posttraumatic stress disorder (PTSD) symptoms (PTSD) and chronic pain in firefighters to inform prevention and intervention efforts. Methods The current sample included 155 firefighters (93.5% male; Mage = 42.2, SD = 9.8) recruited online from career, volunteer, and combination (i.e., volunteer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…and can sustain them as they navigate their unique journeys toward healing and recovery. Hope is an influential factor in perseverance and is closely linked with resilience (Cohen, 2017;Ozturk et al, 2022;Senger et al, 2023). Prominent models of hope such as Charles Snyder's Hope Theory and the Herth Hope Index concur that hope is multidimensional and involves at a minimum two factors: (a) a future focused sense of expectancy and (b) interconnection (Feldman et al, 2023).…”
Section: Spirituality Can Be a Source Of Peace And Hope For Those We ...mentioning
confidence: 99%
“…and can sustain them as they navigate their unique journeys toward healing and recovery. Hope is an influential factor in perseverance and is closely linked with resilience (Cohen, 2017;Ozturk et al, 2022;Senger et al, 2023). Prominent models of hope such as Charles Snyder's Hope Theory and the Herth Hope Index concur that hope is multidimensional and involves at a minimum two factors: (a) a future focused sense of expectancy and (b) interconnection (Feldman et al, 2023).…”
Section: Spirituality Can Be a Source Of Peace And Hope For Those We ...mentioning
confidence: 99%
“…High resilience levels have been reported as a protective factor from psychopathology (Agaibi & Wilson, 2005 ; Hoge et al, 2007 ; Horn et al, 2016 ). In FRs, research has shown that resilience is associated with perceived wellness (O’Neil & Kruger, 2022 ) and is considered protective for stress-related pathologies (Green et al, 2010 ; Lee et al, 2016 ; McCanlies et al, 2014 ; Oh et al, 2022 ; Pietrzak et al, 2009 , 2010 ) that can explain up-to ∼30% of the variance with regard to mental health outcomes in this population (Senger et al, 2023 ; Streb et al, 2014 ). Furthermore, resilience has been shown to moderate the mediation effect between traumatic stress and PTSD symptoms via perceived stress and to buffer the impact of traumatic events on the development of PTSD (Lee et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%